PROFILE OF PATIENTS WHO UNDERGO SEE AND TREAT PROGRAMME IN PUSKESMAS MENGWI I IN 2017-2018 - Dampati, Putu Srinata; Budiana, I Nyoman Gede; Mahendra, I Nyoman Bayu; Manuaba, I. B. G. Fajar (E-Jurnal Medika Udayana; Vol 10 No 12 (2021): Vol 10 No 12(2021): E-Jurnal Medika UdayanaDO - 10.24843/MU.2021.V10.i12.P09, 2021)
Cervical cancer is  one of the high incidence cancer in the world including Indonesia. The mortality of this cancer is also high. In order to decrease number of incidence and mortality rate, prevention must be done. Cervical cancer prevention can be conducted through early detection/screening of precancer lesion. See and treat is one of the screening method to prevent cervical cancer development. This method uses Visual Inspection with Acetic Acid (VIA) for screening and cryotherapy as a treatment if VIA test show positive result. The goal of this study is to determine profile of patients who undergo see and treat programme in Puskesmas Mengwi I in 2017-2018. This study is a descriptive cross sectional study using secondary data obtained from patient’s medical record who undergo see and treat programme in Puskesmas Mengwi I in 2017-2018. Sample taken using total sampling technique. There are 155 patients (1.39%) which obtained from this study from 11,146 total female population in Puskesmas Mengwi I working area, about 84 patients (54.2%) are > 35 years old, 142 patients (91.6%) first married at the age ? 20, 94 patients (60.6%) have graduated college, 105 patients (67.7%) are currently working, 76 patients (49.0%) using IUD, 43 patients (27.7%) had no gynecological complain, 91 patients (58.7%) have < 3 children, 10 patients (6.5%) show positive VIA result, and all of the VIA positive patient (100%) treated using cryotherapy. Keywords : see and treat, VIA, cryotherapy.